Kinematics and Aerodynamics of Dragonflies (Pantala flavescens, Libellulidae) in Climbing Flight - Peng, Liansong; Pan, Tianyu; Zheng, Mengzong; Song, Shiying; Su, Guanting; Li, Qiushi (Frontiers in Bioengineering and Biotechnology, 2022)
This study presents a detailed analysis of dragonflies’ climbing flight by integratinghigh-speed photogrammetry, three-dimensional reconstruction, and computational fluid dynamics. In this study, a dragonfly’s climbing flight is captured by two high-speed cameras with orthogonal optical axes. Through feature point matching and three-dimensional reconstruction, the body kinematics and wing kinematics of 22 dragonflies in climbing flight are accurately captured. Experimental results show that the climbing angles (η) are distributed from 10° to 80° and are concentrated within two ranges, 60°–70° (36%) and 20°–30° (32%), which are defined as large angle climb (LAC) and small angle climb (SAC), respectively. In order to study the aerodynamic mechanism of the climbing flight based on the biological observation results, the kinematic parameters of the dragonfly during LAC and SAC are selected for analysis and numerical simulation. The results show that the climbing angle η and wing kinematics are related. There are considerable differences in wing kinematics during climbing with different η, while the wing kinematics are unchanged during climbing with similar η. With the increase in η, the phase difference (λ) between the forewing and the hind wing decreases and the amplitude of the positional angle (θmean) of the hind wing increases, while θmean of the forewing remains almost unchanged. Through numerical simulation of LAC and SAC, it can be found that during the climb with different η, the different wing kinematics have a significant influence on aerodynamic performance. During SAC, the increase in λ and the decrease in θmean of the hind wing weaken the aerodynamic disturbance of the forewing by the vortex wing of the hind wing, thus improving the flight efficiency.